(untitled) (Research, Society and Development, 2016)
Teachers are the mediators of teaching and learning processes in stages of basic education or higher education. These mediations as educational functions of teaching are subsidized by conceptions, in other words, their understanding about teaching and learning guides their planning, speeches and activities in schools. This study’s objective is to analyze the concepts of teaching and learning of undergraduate students from the Federal University of Rio Grande do Norte through two school situations. The methodological way was outlined through the fundamentals of a descriptive and analytical research of the degree courses students conceptions from UFRN. The instrument used for data collection was a questionnaire applied to 80 students of undergraduations from the exact, humanistic and health areas. We defend training processes that enables future teachers theoretical appropriation moments through the contributions of educational psychology and practical experiences, in which teachers in training can reflect about practical situations according to the various contributions of pedagogical knowledge fields.